A laser-driven optical atomizer: photothermal generation and transport of zeptoliter-droplets along a carbon nanotube deposited hollow optical fiber. Issue 13 (18th March 2022) - Lee, Hyeonwoo; Partanen, Mikko; Lee, Mingyu; Jeong, Sunghoon; Lee, Hyeung Joo; Kim, Kwanpyo; Ryu, Wonhyoung; Dholakia, Kishan; Oh, Kyunghwan
Abstract : This paper presents a novel atomizing methodology along the single strand of an optical fiber integrated with single-walled carbon nanotubes. Based on this photonic device, numerous droplets generation with zeptoliter volume scale was confirmed. Abstract : From mechanical syringes to electric field-assisted injection devices, precise control of liquid droplet generation has been sought after, and the present state-of-the-art technologies have provided droplets ranging from nanoliter to subpicoliter volume sizes. In this study, we present a new laser-driven method to generate liquid droplets with a zeptoliter volume, breaking the fundamental limits of previous studies. We guided an infrared laser beam through a hollow optical fiber (HOF) with a ring core whose end facet was coated with single-walled carbon nanotubes. The laser light was absorbed by this nanotube film and efficiently generated a highly localized microring heat source. This evaporated the liquid inside the HOF, which rapidly recondensed into zeptoliter droplets in the surrounding air at room temperature. We spectroscopically confirmed the chemical structures of the liquid precursor maintained in the droplets by atomizing dye-dissolved glycerol. Moreover, we explain the fundamental physical principles as well as functionalities of the optical atomizer and perform a detailed characterization of the droplets. Our approach has strong prospects for nanoscale delivery of biochemical substances in minuscule zeptoliter volumes.